Genome-wide association study for ashy stem blight resistance in USDA common bean germplasm - Shi, Ainong; Viteri, Diego M.; Linares-Ramírez, Angela M.; Xiong, Haizheng; Chen, Senyu (Frontiers in Plant Science, 2025)
Ashy stem blight (ASB), caused by the fungus Macrophomina phaseolina (Tassi) Goidanich, poses a significant threat to common bean (Phaseolus vulgaris L.) cultivation worldwide. Due to the limited effectiveness of fungicides against ASB, the development of genetically resistant cultivars offers an eco-friendly and sustainable management strategy. This study aimed to accelerate genetic improvement in common bean by integrating molecular breeding tools with conventional breeding approaches to enhance ASB resistance. A total of 335 common bean germplasm accessions from the United States Department of Agriculture (USDA) Germplasm Resources Information Network (GRIN) collection were evaluated for their response to the PRI21 M. phaseolina isolate. A genome-wide association study (GWAS) was conducted using 87,193 high-quality single-nucleotide polymorphisms (SNPs) and four statistical models—Bayesian-information and Linkage-disequilibrium Iteratively Nested Keyway (BLINK), mixed linear model (MLM), multiple-locus MLM (MLMM), and general linear model (GLM)—implemented in GAPIT3. Twenty-three accessions had intermediate resistance, with Andean PI 173208 and PI 264786 showing the lowest disease severity scores (<3.7) to PRI21. Four quantitative trait loci (QTLs) were identified on chromosomes Pv02, Pv04, Pv05, and Pv10 across all accessions. Additionally, three QTLs were detected on Pv01, Pv02, and Pv11 in Mesoamerican accessions, while three QTLs were found on Pv02, Pv04, and Pv06 in Andean accessions. The two candidate genes Phvul.002G046300 [leucine-rich repeat (LRR) family protein] and Phvul.002G046500 (receptor-like protein kinase 1) were identified on chromosome Pv02 as being associated with ASB resistance. These SNP markers linked to these QTLs may be valuable for marker-assisted selection in common bean breeding programs aimed at improving ASB resistance.